Remittances as Social Practices and Agents of Change The Future of Transnational Society - Meyer, Silke; Ströhle, Claudius (2023)
Remittances are conceptualized as flows of money, objects, ideas, traditions, and symbolic capital, mapping out a crossborder space in which people live, work, and communicate with multiple belongings. However, their power to improve individual living conditions and community infrastructure mainly results from global inequality and this remittance mantra needs to be challenged by going beyond the migration-development-nexus and by revealing dependencies and frictions in remittance relations. Remittances are thus scrutinized in their effects on both social cohesion and social rupture, and by highlighting the transformative effects of remittance in the context of conflict, climate change, and the postcolonial, we shed light on the future of transnational society.